Automated treatment of film tear in degraded archived media - KOKARAM, ANIL CHRISTOPHER (IEEE, 2004)
A common form of degradation in archived film is film tear. This is caused by the physical ripping of the film. Tear causes displacement of a region of the degraded frame and the loss of image data. As of yet no method of automatically treating film tear has been proposed. This paper outlines an algorithm to automatically detect and restore torn frames. Tear detection is facilitated by the presence of a large edge feature, unlikely to be caused by other forms of degradation, in the torn frame. Restoration is achieved by estimating the regional displacement and recovering missing image data.
PUBLISHED
Keywords: cinematography; edge detection